Dietary Riboflavin Requirement of Pacific White Shrimp (Litopenaeus vannamei) - Kokila Sanjeewani; Kyeong-Jun Lee (Aquaculture Nutrition)
This study was conducted to determine the dietary riboflavin requirement and its effects on growth performance, feed utilization, innate immunity, and diet digestibility of Litopenaeus vannamei. A riboflavin-free basal diet (R0) was formulated as a control, and six other diets were prepared by adding riboflavin of 10, 20, 30, 40, 50, and 60 mg/kg to the basal diet (designated as R10, R20, R30, R40, R50, and R60, respectively). Quadruplicate groups of shrimp (initial average weight 0.17±0.00 g) were fed the diets six times a day for 8 weeks. Weight gain, specific growth rate, and protein efficiency ratio were significantly increased by riboflavin (p<0.05). The maximum values were observed in shrimp fed R40 diet. The highest activities of phenoloxidase, nitro blue tetrazolium, superoxide dismutase, and glutathione peroxidase were observed in shrimp fed R40 diet. Lysozyme activity was significantly higher in shrimp fed R30 and R40 diets than that of shrimp fed R60 diet (p<0.05). Intestinal villi were significantly longer in shrimp fed R50 and R60 diets compared to those of all other groups while the shortest villi were observed in R0 group (p<0.05). Intestinal villi were clearly distinguished in shrimp fed higher levels of riboflavin compared to those of shrimp fed R0 and R10 diets. Apparent digestibility coefficients of dry matter and protein in diets were not significantly affected by riboflavin levels (p<0.05). Whole-body proximate composition and hemolymph biochemical parameters were not significantly altered by dietary riboflavin (p<0.05). Therefore, the results of this study indicate that riboflavin is essential to enhance growth performance, feed utilization, nonspecific immunity, and intestine morphology of shrimp. An optimal riboflavin requirement for the maximum growth of L. vannamei seems to be approximately 40.9 mg/kg diet.